Determination of the mimic epitope of the M-like protein adhesin in swine Streptococcus equi subsp. zooepidemicus - Fan, Hongjie (BioMed Central, 2008)
BACKGROUND: The M-like protein, also known as SzP, is expressed on the surface of Streptococcus equi subsp. zooepidemicus (S. zooepidemicus). Previous studies demonstrated that SzP is similar to M protein of group A Streptococcus in the structure and characteristics of antiphagocytosis. The M protein is an adhesin that can bind to the host cells, however it is not known whether the SzP of S. zooepidemicus also functions as an adhesin. We conducted an investigation to determine SzP as an adhesin, and one SzP epitope was identified to be responsible for mediating binding to HEp-2 cells. METHODS: The gene encoding SzP was expressed in E. coli, and the purified recombinant SzP (rSzP) was recognized by rabbit anti-S. zooepidemicus antibodies using immunoblot. Furthermore, the adherence of S. zooepidemicus to HEp-2 cells was inhibited by anti-rSzP antibodies in a dose-dependent manner. We employed a random 12-peptide phage display library for screening of immunodominant mimics of the SzP, which were recognized by an anti-SzP specific monoclonal antibody (mAb 2C8). Initial positive phage clones were identified by ELISA, followed by assays to determine the adherence-inhibiting ability of the peptide. RESULTS: Ten out of fourteen selected positive clones showed high reactivity that effectively inhibited the binding of mAb 2C8 to rSzP. The motif XSLSRX was highly conserved among six of the ten clones. CONCLUSION: Collectively, our findings suggest that the motif XSLSRX may represent an immunodominant mimic epitope of the SzP of S. zooepidemicus strain ATCC 35246, and that the same epitope may be used to mediate SzP binding to HEp-2 cells.